MENINGKATKAN MOTIVASI DAN KARAKTER WASAKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DAN NUMBERED HEAD TOGETHER TERINTEGRASI STEM PADA MUATAN IPA KELAS VB SDN-SN SUNGAI MIAI 5 BANJARMASIN - Sarah, Zeni; Muhsinah Annisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is that children's motivation in the learning process is still low, children are lazy in doing the tasks given, lack of concentration on learning, children are not motivated to be able to learn independently to solve problems in their daily lives which results in many children not being actively involved in the process learning. The cause is that learning rarely involves students in discussions, conducting experiments using media or other teaching aids which results in a lack of student skills, especially motivation, so that students can receive the material well. This research aims to determine motivation and character of students by implementing the Problem Based Learning and Numbered Head Together model. This research used Classroom Action Research which was carried out in 2 cycles. This type of research data is qualitative and quantitative data, through measurement techniques with written tests on individual motivation and observation of wasaka character in students. The results of this research show that student motivation has reached a percentage of 94.11%, that is, it has met the classical success indicators, namely ≥80% and affective learning outcomes have reached a percentage of 94.11%, that is, they have met the classical success indicators, namely ≥80%. Based on these results, it can be concluded that the use of the STEM Integrated Problem Based Learning and Numbered Head Together model can increase student motivation and students character.